The role of modernization of social and labor relations in achieving the goals of sustainable socio-economic development - Zgalat-Lozynska, L.; Lych, V.; Holovach, N (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the theoretical, methodological and applied substantiation of the role of modernising social and labour relations in achieving the goals of sustainable socio-economic development of Ukraine. The paper shows that the quality of social and labour relations determines the economy’s capacity to ensure decent work, inclusiveness, productivity and social cohesion, and thus the speed and resilience of post-war recovery. The key challenges are systematised as follows: outdated regulatory approaches, a high share of informal employment, weak wage-payment discipline and the gender pay gap, fragile mechanisms of social dialogue, skill shortages in the context of the digital and “green” transitions, as well as the consequences of the full-scale war for the labour market. Modern scholarly approaches and international practices are summarised, in particular the concepts of “decent work”, “flexicurity” and the “just transition”, which propose a balance between flexibility and social security and set the framework for the institutional renewal of social and labour relations. It is shown that the modernisation of social and labour relations should proceed simultaneously in the economic, social and environmental dimensions: through a fair and transparent remuneration system, enhanced social protection, the development of collective-bargaining regulation and tripartite partnership, as well as via tools of active labour-market policy and lifelong learning. A logical-structural model of modernisation is proposed that integrates legal, institutional, organisational-managerial and educational solutions: updating labour legislation on the principles of flexicurity; expanding the powers and responsibilities of the parties to social dialogue; introducing a National Decent Work Programme; investing in human capital (micro-credentials, training vouchers, dual education); the digital transformation of HR processes; and inclusive programmes for integrating veterans and internally displaced persons. The expected effects of these measures are demonstrated: productivity growth, improved job quality, reduced inequality and strengthened innovation capacity. The novelty of the article lies in combining the institutional and competence-based approaches with a project-oriented implementation logic, which makes it possible to convert strategic principles into concrete policy tools and enterprise practices. The practical significance consists in the formulated priorities and evaluation indicators that can be used by the government, social partners and business to design programmes for modernising social and labour relations in post-war recovery and for convergence with EU standards.